The Milk Thistle (Silybum marianum) Compound Silibinin Inhibits Cardiomyogenesis of Embryonic Stem Cells by Interfering with Angiotensin II Signaling - Enas Hussein Ali; Fatemeh Sharifpanah; Amer Taha; Suk Ying Tsang; Maria Wartenberg; Heinrich Sauer (Hindawi Limited, 2018)
The milk thistle (Silybum marianum (L.) Gaertn.) compound silibinin may be an inhibitor of the angiotensin II type 1 (AT1) receptor which is expressed in differentiating embryonic stem (ES) cells and is involved in the regulation of cardiomyogenesis. In the present study, it was demonstrated that silibinin treatment decreased the number of spontaneously contracting cardiac foci and cardiac cell areas differentiated from ES cells as well as contraction frequency and frequency of calcium (Ca2+) spiking. In contrast, angiotensin II (Ang II) treatment stimulated cardiomyogenesis as well as contraction and Ca2+ spiking frequency, which were abolished in the presence of silibinin. Intracellular Ca2+ transients elicited by Ang II in rat smooth muscle cells were not impaired upon silibinin treatment, excluding the possibility that the compound acted on the AT1 receptor. Ang II treatment activated extracellular signal-regulated kinase 1/2 (ERK1/2), c-Jun NH2-terminal kinase (JNK), and p38 mitogen-activated protein kinase (MAPK) pathways in embryoid bodies which were abolished upon silibinin pretreatment. In summary, our data suggest that silibinin inhibits cardiomyogenesis of ES cells by interfering with Ang II signaling downstream of the AT1 receptor.